Positive electrode for non-aqueous electrolyte secondary battery and non-aqueous electrolyte secondary battery

JP7645821B2Active Publication Date: 2025-03-14PANASONIC HOLDINGS CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021574636
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-01-31
Filing Date
2021-01-18
Publication Date
2025-03-14
Estimated Expiration
2041-01-18

Smart Images

  • Figure 0007645821000005
    Figure 0007645821000005
  • Figure 0007645821000006
    Figure 0007645821000006
  • Figure 0007645821000007
    Figure 0007645821000007
Patent Text Reader

Abstract

This positive electrode for nonaqueous electrolyte secondary batteries is provided with a positive electrode core body and a positive electrode mixture layer that is formed on the surface of the positive electrode core body. The positive electrode mixture layer contains a positive electrode active material that is mainly composed of a lithium transition metal composite oxide which contains 70% by mole or more of Ni relative to the total number of moles of the metal elements excluding Li. In addition, the positive electrode core body has a thermal conductivity X of from 50 to 155 W / m∙K (25°C). It is preferable that the upper limit Y1 and the lower limit Y2 of the median value Y in the circularity distribution of the lithium transition metal composite oxide relative to the thermal conductivity X of the core body respectively satisfy the conditions of formula (1) and formula (2) described below. Formula (1): Y1 = 0.9322(X-0.987) Formula (2): Y2 = 0.1613(X-0.746) – 0.0005
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a positive electrode for a non-aqueous electrolyte secondary battery and a non-aqueous electrolyte secondary battery using the positive electrode. [Background technology]

[0002] The positive electrode of the non-aqueous electrolyte secondary battery includes a positive electrode core and a positive electrode composite layer formed on the surface of the positive electrode core. In the non-aqueous electrolyte secondary battery, for example, due to the inclusion of conductive foreign matter or nail penetration, the positive electrode core and the negative electrode come into contact with each other, causing a low-resistance internal short circuit through which a large current flows, and a large amount of heat (Joule heat) may occur. When this heat is transmitted to the positive electrode active material, the active material decomposes to generate oxygen, which may react with the active lithium in the negative electrode active material to cause a chain reaction of heat generation called thermal runaway. Such heat generation may be particularly problematic in batteries with high energy density.

[0003] In view of this situation, various measures have been taken in non-aqueous electrolyte secondary batteries to suppress heat generation in the event of an abnormality. For example, Patent Document 1 proposes a non-aqueous electrolyte secondary battery having a positive electrode core whose average composition obtained by averaging the ratio of elements constituting the positive electrode core in the thickness direction of the core is equal to the composition of an alloy whose liquidus temperature is 630°C or less, that is, a positive electrode core that melts at a temperature of 630°C or less. Patent Document 1 describes that when an internal short circuit occurs and heat is generated, the core melts and shrinks at that part, eliminating the internal short circuit, and thus heat generation during an internal short circuit can be suppressed. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 4953631 Summary of the Invention

[0005] As disclosed in Patent Document 1, it is expected that by lowering the melting point of the positive electrode core, the core will melt quickly at the short-circuited area and the internal short circuit will be resolved. However, there is a concern that before the core melts, the heat from the short-circuited area will be transferred to the positive electrode active material, causing the active material to decompose, leading to thermal runaway.

[0006] The positive electrode for a nonaqueous electrolyte secondary battery according to the present disclosure is a positive electrode including a core and a composite layer formed on a surface of the core, the composite layer containing a positive electrode active material mainly composed of a lithium transition metal composite oxide in which the ratio of Ni to the total number of moles of metal elements excluding Li is 70 mol % or more, and the core has a thermal conductivity X of 50 to 155 W / m K (25° C.).

[0007] In the positive electrode for a nonaqueous electrolyte secondary battery according to the present disclosure, it is preferable that an upper limit Y1 and a lower limit Y2 of a median value Y in a circularity distribution of the lithium transition metal composite oxide with respect to the thermal conductivity X of the core satisfy the conditions of the following (Formula 1) and (Formula 2), respectively.

[0008] (Formula 1)Y1=0.9322(X -0.987 ) (Formula 2)Y2=0.1613(X -0.746 )-0.0005 The nonaqueous electrolyte secondary battery according to the present disclosure includes the above positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and a nonaqueous electrolyte.

[0009] The positive electrode according to the present disclosure can suppress heat generation in the battery when an internal short circuit occurs to a greater extent. In a nonaqueous electrolyte secondary battery using the positive electrode according to the present disclosure, even if an internal short circuit occurs due to, for example, a nail being pierced, decomposition of the positive electrode active material and expansion of the short circuit portion are unlikely to occur, and transition to thermal runaway can be sufficiently prevented. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a perspective view showing the appearance of a nonaqueous electrolyte secondary battery according to an embodiment. [Diagram 2] FIG. 2 is a perspective view of an electrode assembly according to an embodiment. [Figure 3A] FIG. 3A is a cross-sectional view of a positive electrode according to an example of an embodiment, showing a state in which a nail is inserted. [Figure 3B] FIG. 3B is a cross-sectional view of a positive electrode according to an example of an embodiment, showing a state in which a nail is inserted. [Figure 4] FIG. 4 is a diagram showing the relationship between the thermal conductivity of the positive electrode core and the circularity of the positive electrode active material, which influence heat generation upon the occurrence of an internal short circuit in a nonaqueous electrolyte secondary battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] As described above, when an internal short circuit occurs due to nail penetration or the like, it is an important issue to suppress the decomposition of the positive electrode active material, the expansion of the short circuit, and to prevent the transition to thermal runaway. In particular, in a battery using a positive electrode active material with a high Ni content, heat generation is likely to increase when an internal short circuit occurs, so it is necessary to more reliably prevent thermal runaway. As a result of intensively studying such an issue, the present inventors have found that the thermal conductivity of the positive electrode core body has a significant effect on the heat generation of the battery. And, by setting the thermal conductivity of the positive electrode core body within the range of 50 to 155 W / m·K (25°C), it has been found that the heat generation of the battery when an internal short circuit occurs can be significantly suppressed without impairing the battery performance such as input / output characteristics.

[0012] According to the non-aqueous electrolyte secondary battery using the positive electrode according to the present disclosure, by using a positive electrode core having a thermal conductivity within the above range, the positive electrode core melts before the heat of the short circuit portion is transferred to the positive electrode active material and the active material is violently decomposed. This is thought to interrupt the current path between the positive electrode core and the negative electrode, preventing the transition to thermal runaway. In addition, as a result of the study by the present inventors, it was found that the melting of the positive electrode core is greatly influenced by the thermal conductivity of the positive electrode core as well as the penetration of the positive electrode active material into the positive electrode core. Since the penetration amount of the positive electrode active material can be adjusted by controlling the circularity of the active material, the heat generation of the battery when an internal short circuit occurs can be more significantly suppressed by controlling the circularity of the positive electrode active material to an appropriate range based on the above (Equation 1) and (Equation 2) together with the thermal conductivity of the positive electrode core.

[0013] Hereinafter, an example of an embodiment of a positive electrode for a nonaqueous electrolyte secondary battery according to the present disclosure and a nonaqueous electrolyte secondary battery using the positive electrode will be described in detail with reference to the drawings. It is assumed from the beginning that the multiple embodiments and modified examples described below will be selectively combined.

[0014] Fig. 1 is a perspective view showing the appearance of a nonaqueous electrolyte secondary battery 10 according to an embodiment, and Fig. 2 is a perspective view of an electrode assembly 11 constituting the nonaqueous electrolyte secondary battery 10. The nonaqueous electrolyte secondary battery 10 shown in Fig. 1 includes a bottomed, rectangular cylindrical exterior can 14 as an exterior body, but the exterior body is not limited thereto. The nonaqueous electrolyte secondary battery according to the present disclosure may be, for example, a cylindrical battery including a bottomed, cylindrical exterior can, a coin battery including a coin-shaped exterior can, or a laminate battery including an exterior body formed of a laminate sheet including a metal layer and a resin layer.

[0015] As shown in FIG. 1 and FIG. 2, the nonaqueous electrolyte secondary battery 10 includes an electrode body 11, a nonaqueous electrolyte, a bottomed rectangular cylindrical exterior can 14 that accommodates the electrode body 11 and the nonaqueous electrolyte, and a sealing plate 15 that closes the opening of the exterior can 14. The nonaqueous electrolyte secondary battery 10 is a so-called prismatic battery. The electrode body 11 has a wound structure in which a positive electrode 20 and a negative electrode 30 are wound with a separator 40 interposed therebetween. The positive electrode 20, the negative electrode 30, and the separator 40 are all strip-shaped long bodies, and the positive electrode 20 and the negative electrode 30 are wound with the separator 40 interposed therebetween. The electrode body may be a laminated type in which a plurality of positive electrodes and a plurality of negative electrodes are alternately laminated one by one with a separator interposed therebetween.

[0016] The nonaqueous electrolyte secondary battery 10 includes a positive electrode terminal 12 electrically connected to the positive electrode 20 via a positive electrode current collector 25, and a negative electrode terminal 13 electrically connected to the negative electrode 30 via a negative electrode current collector 35. In this embodiment, the sealing plate 15 has an elongated rectangular shape, with the positive electrode terminal 12 disposed at one end in the longitudinal direction of the sealing plate 15 and the negative electrode terminal 13 disposed at the other end in the longitudinal direction of the sealing plate 15. The positive electrode terminal 12 and the negative electrode terminal 13 are external connection terminals electrically connected to other nonaqueous electrolyte secondary batteries 10, various electronic devices, etc., and are attached to the sealing plate 15 via insulating members.

[0017] For ease of explanation, the height direction of the exterior can 14 will be referred to as the "vertical direction" of the nonaqueous electrolyte secondary battery 10, the sealing plate 15 side will be referred to as the "top", and the bottom side of the exterior can 14 will be referred to as the "bottom". In addition, the direction along the longitudinal direction of the sealing plate 15 will be referred to as the "lateral direction" of the nonaqueous electrolyte secondary battery 10.

[0018] The exterior can 14 is a metal container in the shape of a rectangular cylinder with a bottom. An opening formed at the upper end of the exterior can 14 is closed, for example, by welding a sealing plate 15 to the edge of the opening. The sealing plate 15 is generally provided with a liquid injection part 16 for injecting a non-aqueous electrolyte, a gas exhaust valve 17 for opening and exhausting gas when an abnormality occurs in the battery, and a current interruption mechanism. The exterior can 14 and the sealing plate 15 are made of a metal material containing aluminum as a main component, for example.

[0019] The electrode body 11 is a flat-shaped wound electrode body including a flat portion and a pair of curved portions. The electrode body 11 is housed in the outer can 14 with the winding axis direction aligned with the lateral direction of the outer can 14 and the width direction of the electrode body 11 in which the pair of curved portions are aligned aligned with the height direction of the battery. In this embodiment, a positive electrode side current collector formed by laminating the core exposed portion 23 of the positive electrode 20 at one axial end of the electrode body 11 and a negative electrode side current collector formed by laminating the core exposed portion 33 of the negative electrode 30 at the other axial end are formed, and each current collector is electrically connected to a terminal via a current collector. An insulating electrode body holder (insulating sheet) may be disposed between the electrode body 11 and the inner surface of the outer can 14.

[0020] Hereinafter, the electrode body 11, particularly the positive electrode 20, will be described in detail with reference to Fig. 3A, Fig. 3B, and Fig. 4 as appropriate. Fig. 3A and Fig. 3B are cross-sectional views of the positive electrode 20, showing a state in which a nail 100 is inserted. For convenience of explanation, Fig. 3A and Fig. 3B show only six particles of the positive electrode active material 24, but in reality, the positive electrode mixture layer 22 is filled with a large number of particles. Fig. 4 is a diagram showing the relationship between the thermal conductivity of the positive electrode core 21 and the circularity of the positive electrode active material 24, which affect heat generation when an internal short circuit occurs.

[0021] [Positive electrode] As shown in FIG. 3A and FIG. 3B, the positive electrode 20 has a positive electrode core 21 and a positive electrode composite layer 22 formed on the surface of the positive electrode core 21. The positive electrode core 21 is composed of a metal foil mainly composed of, for example, Al, Mg, or the like. The positive electrode composite layer 22 contains a positive electrode active material 24, a conductive material, and a binder, and is preferably provided on both sides of the positive electrode core 21. The positive electrode 20 can be produced, for example, by applying a positive electrode composite slurry containing the positive electrode active material 24, a conductive material, a binder, and the like onto the positive electrode core 21, drying the coating, and then compressing it to form a positive electrode composite layer on both sides of the positive electrode core 21.

[0022] A metal foil having a thermal conductivity X of 50 to 155 W / m·K (25° C.) is used for the positive electrode core 21. If the thermal conductivity X of the positive electrode core 21 exceeds 155 W / m·K, the positive electrode core 21 is less likely to melt at the short circuit portion, and as a result, heat is transferred to the positive electrode active material 24, the active material is decomposed, and the amount of heat generated by the battery increases. On the other hand, if the thermal conductivity X falls below 50 W / m·K, the plate resistance increases significantly and the input / output characteristics of the battery decrease. In other words, only when a positive electrode core 21 having a thermal conductivity X in the range of 50 to 155 W / m·K is used, heat generation by the battery when an internal short circuit occurs can be significantly suppressed without impairing battery performance such as input / output characteristics.

[0023] The positive electrode core 21 may be any metal foil that satisfies the condition of the thermal conductivity X, and is composed of a metal foil made of an alloy containing various metal elements such as Al, Mn, Cu, Mg, Zr, Si, Cr, Ti, Fe, and Ni. An example of a suitable metal foil is a metal foil made of an Al-Mg alloy containing Al or Mg as the main component (for example, a solid solution of Al and Mg, or a solid solution of Al and Mg partially containing Al3Mg2). In this specification, the main component means the component with the highest mass ratio. In the positive electrode core 21 containing Al, the content of Al may be 5 to 95 mass%. In the positive electrode core 21 containing Mg, the content of Mg may be 1.5 to 90 mass%. The positive electrode core 21 is composed of a metal foil containing, for example, Al and Mg, and further containing other metal elements.

[0024] As described above, the thermal conductivity X of the positive electrode core 21 is 50 to 155 W / m·K (25°C). When emphasis is placed on suppressing heat generation during an internal short circuit, the thermal conductivity X is preferably 150 W / m·K or less, more preferably 130 W / m·K or less, and particularly preferably 100 W / m·K or less. The thermal conductivity X of the positive electrode core 21 can be adjusted by changing the ratio of metal elements constituting the metal foil, for example, the ratio of Al and Mg. The thickness of the positive electrode core 21 is not particularly limited, but a suitable example of the thickness is 5 to 20 μm, or 8 to 15 μm.

[0025] The positive electrode active material 24 is mainly composed of a lithium transition metal composite oxide in which the ratio of Ni to the total number of moles of metal elements excluding Li is 70 mol % or more. A lithium transition metal composite oxide with a Ni content of 70 mol % or more has a high energy density, and by using this as the main component of the positive electrode active material 24, it is possible to increase the capacity of the battery. The Ni content is, for example, 70 to 95 mol % to the total number of moles of metal elements excluding Li. The positive electrode active material 24 may be composed only of the composite oxide, or may contain a composite oxide with a Ni content of less than 70 mol % as long as it does not impair the object of the present disclosure.

[0026] The lithium transition metal composite oxide may contain elements other than Li and Ni. Examples of other metal elements include Co, Mn, Al, Zr, W, Si, Mg, P, B, Ti, Mo, Sc, Y, Fe, Cu, Zn, Cr, Pb, etc. Among them, it is preferable to contain at least one of Co and Mn, and in addition to these, Al, W, Zr, B, etc. may be contained. Examples of suitable lithium transition metal composite oxides are NCA-based composite oxides containing Ni, Co, and Al, and NCM-based composite oxides containing Ni, Co, and Mn.

[0027] The volume-based median diameter (D50) of the lithium transition metal composite oxide is, for example, 1 to 30 μm, and preferably 5 to 15 μm. The D50 of the lithium transition metal composite oxide is measured using a laser diffraction / scattering type particle size distribution measuring device (LA960 manufactured by Horiba, Ltd.) with water as a dispersion medium. The median circularity of the lithium transition metal composite oxide is, for example, 0.30 or more, preferably 0.40 or more, and more preferably 0.45 or more. The median circularity is less than 1. The circularity of the lithium transition metal composite oxide is measured using a wet flow type particle size / shape analyzer (FPIA3000 manufactured by Sysmex) with water as a dispersion medium.

[0028] As shown in FIG. 3A and FIG. 3B, a part of the positive electrode active material 24 is embedded in the positive electrode core 21. The degree of this embedment affects the melting property of the positive electrode core 21, and the greater the amount of the positive electrode active material 24 embedded in the positive electrode core 21 and the greater the depth of the embedment, the easier it is for the positive electrode core 21 to melt at the short-circuited portion when an internal short circuit occurs in the battery. The positive electrode core 21 into which the positive electrode active material is embedded has a thinner portion, so that the amount of heat required for melting is reduced, and melting is facilitated. The degree of embedment of the positive electrode active material 24 into the positive electrode core 21 is greatly affected by the circularity of the positive electrode active material 24 (lithium transition metal composite oxide), and generally, the higher the circularity, the greater the degree of embedment.

[0029] In other words, the thermal conductivity X of the positive electrode core 21 and the circularity of the positive electrode active material 24 are important factors in the melting property of the positive electrode core 21 and thus in suppressing heat generation when an internal short circuit occurs. As illustrated in FIG. 3A, when a nail 100 is pierced into the electrode body 11 and the positive electrode core 21 and the negative electrode 30 are in electrical contact with each other, a large current flows and Joule heat occurs. If this heat is transmitted to the positive electrode mixture layer 22 via the positive electrode core 21, the positive electrode active material 24 may decompose and lead to thermal runaway. However, according to this embodiment, as illustrated in FIG. 3B, the positive electrode core 21 is quickly melted before the heat of the short circuit portion is transmitted to the positive electrode active material 24 and the active material is violently decomposed. As a result, the current path between the positive electrode core 21 and the negative electrode 30 is interrupted, and it is considered that heat generation in the battery is significantly suppressed.

[0030] As shown in FIG. 4, it is preferable that the upper limit Y1 and lower limit Y2 of the median value in the circularity distribution of the lithium transition metal composite oxide with respect to the thermal conductivity X of the positive electrode core 21 satisfy the conditions of the following (Formula 1) and (Formula 2), respectively.

[0031] (Formula 1)Y1=0.9322(X -0.987 ) (Formula 2)Y2=0.1613(X -0.746 )-0.0005 In relation to the thermal conductivity X of the positive electrode core 21, by adjusting the median value of the circularity of the lithium transition metal composite oxide so as to satisfy the conditions of (Equation 1) and (Equation 2), the melting property of the positive electrode core 21 at the short-circuit portion is improved, and heat generation in the battery is more significantly suppressed.

[0032] The lithium transition metal composite oxide includes, for example, a composite oxide composed of secondary particles formed by agglomeration of primary particles a1 (hereinafter referred to as "lithium transition metal composite oxide A"), and a composite oxide composed of a single particle composed of one primary particle b1 or composed of agglomeration of five or less primary particles b1 (hereinafter referred to as "lithium transition metal composite oxide B"). The primary particles a1 constituting the lithium transition metal composite oxide A have a smaller particle diameter than the primary particles b1 constituting the lithium transition metal composite oxide B. For example, the particle diameter of the primary particles b1 is 3 to 5 μm, and the particle diameter of the primary particles a1 is 0.3 to 0.9 μm.

[0033] The particle size of the primary particles of the lithium transition metal composite oxide is measured by embedding the positive electrode 20 in a resin, preparing a cross section of the positive electrode 20 by cross section polisher (CP) processing or the like, and observing the cross section of the positive electrode composite layer 22 in this cross section with a scanning electron microscope (SEM). Then, 20 primary particles are randomly selected from the cross section SEM image. The grain boundaries of the selected 20 primary particles are observed, and the outer shapes of the primary particles are identified, and the major axis of each of the 20 primary particles is calculated, and the average value of these is taken as the particle size of the primary particle. The secondary particles of the lithium transition metal composite oxide A are composed of, for example, 100 to 500,000 primary particles a1 per secondary particle.

[0034] The mass ratio of the lithium transition metal composite oxide B, which is a single particle, to the lithium transition metal composite oxide A, which is a secondary particle, is, for example, 2:8 to 6:4, and preferably 7:3 to 5:5. The lithium transition metal composite oxide may be composed of only one of the lithium transition metal composite oxides A and B. For example, the lithium transition metal composite oxide may be composed of only the lithium transition metal composite oxide B, which is a single particle including a first single particle having a circularity of 0.9 or more and a second single particle having a circularity of less than 0.9. In this case, the mass ratio of the first single particle to the second single particle is, for example, 2:8 to 6:4.

[0035] Lithium transition metal composite oxides are generally produced through a raw material mixing step in which a composite oxide containing a transition metal element such as Ni is mixed with a lithium compound to obtain a raw material mixture, and a firing step in which the raw material mixture is fired to obtain lithium composite oxide particles containing Ni. The particle sizes and circularity of the primary and secondary particles of the lithium transition metal composite oxide are controlled, for example, by controlling the mixing ratio of each raw material in the raw material mixing step.

[0036] When producing the lithium transition metal composite oxide A, for example, the mixing ratio of the Ni-, Mn-containing composite oxide and the lithium compound is adjusted to a molar ratio of metal elements in the Ni-, Mn-containing composite oxide:Li in the range of 1.0:1.0 to 1.0:1.2. On the other hand, when producing the lithium transition metal composite oxide B, for example, the mixing ratio of the Ni-, Mn-containing composite oxide and the lithium compound is adjusted to a molar ratio of metal elements in the Ni-, Mn-containing composite oxide:Li in the range of 1.0:1.0 to 1.0:1.3.

[0037] The particle size and circularity of the primary and secondary particles of the lithium transition metal composite oxide can also be controlled by adjusting the firing temperature in the firing step. When producing lithium transition metal composite oxide A, the firing temperature is set to, for example, a range of 700°C to 1100°C. The firing time in this case is preferably 1 to 48 hours. On the other hand, when producing lithium transition metal composite oxide B, the firing temperature is set to, for example, a range of 800°C to 1100°C. The firing time in this case is preferably 1 to 48 hours.

[0038] The circularity of the positive electrode active material can also be adjusted by sphering the lithium transition metal composite oxide, for example, by Kryptron treatment (Earth Technica Corporation), Jet Mill treatment (Hosokawa Micron Corporation), or Faculty treatment (Hosokawa Micron Corporation).

[0039] Examples of the conductive material contained in the positive electrode mixture layer 22 include carbon materials such as carbon black, acetylene black, ketjen black, and graphite. Examples of the binder contained in the positive electrode mixture layer 22 include fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide resins, acrylic resins, and polyolefin resins. These resins may be used in combination with cellulose derivatives such as carboxymethylcellulose (CMC) or a salt thereof, and polyethylene oxide (PEO).

[0040] [Negative electrode] The negative electrode 30 has a negative electrode core 31 and a negative electrode composite layer formed on the surface of the negative electrode core 31. For the negative electrode core 31, a foil of a metal such as copper that is stable in the potential range of the negative electrode 30 can be used. The negative electrode composite layer contains a negative electrode active material and a binder, and is preferably provided on both sides of the negative electrode core 31. The negative electrode 30 can be produced, for example, by applying a negative electrode composite slurry containing a negative electrode active material, a conductive material, a binder, and the like to the surface of the negative electrode core 31, drying the coating, and then compressing it to form a negative electrode composite layer on both sides of the negative electrode core 31.

[0041] The negative electrode active material is not particularly limited as long as it can reversibly absorb and release lithium ions, and examples thereof include carbon materials such as artificial graphite, natural graphite, amorphous coated graphite, amorphous carbon (low crystalline carbon, amorphous carbon, for example, furnace black, ketjen black, channel black, thermal black, acetylene black, carbon nanotubes, graphene), non-carbon materials such as SiO, and mixtures of carbon materials and non-carbon materials. In the case of a mixture of a carbon material and SiO, the amount of SiO is preferably in the range of, for example, 4 to 70% with respect to the total amount of the mixture. In addition, SiO may contain Li in advance, and the ratio of Si in the Li-Si-O compound is preferably 10 to 80%. In addition, it is preferable that the particle surface of SiO is covered with amorphous carbon (low crystalline carbon, amorphous carbon, etc.).

[0042] As the conductive material contained in the negative electrode mixture layer, carbon materials such as carbon black, acetylene black, ketjen black, and graphite can be used, as in the case of the positive electrode 20. As the binder contained in the negative electrode mixture layer, fluororesin, PAN, polyimide, acrylic resin, polyolefin, and the like can be used, as in the case of the positive electrode 20, but styrene-butadiene rubber (SBR) is preferably used. In addition, the negative electrode mixture layer preferably further contains CMC or a salt thereof, polyacrylic acid (PAA) or a salt thereof, polyvinyl alcohol (PVA), and the like. Among them, it is preferable to use SBR in combination with CMC or a salt thereof, and PAA or a salt thereof.

[0043] [Separator] For example, a porous sheet having ion permeability and insulating properties is used for the separator 40. Specific examples of the porous sheet include a microporous thin film, a woven fabric, and a nonwoven fabric. Suitable materials for the separator 40 include olefin resins such as polyethylene (PE) and polypropylene (PP), and cellulose. The separator 40 may be a laminate such as a PP layer / PE layer / PP layer. The thickness of the separator 40 is preferably in the range of, for example, 5 to 30 μm. In the case of a PP layer / PE layer / PP layer, the thickness of the PP layer is preferably in the range of 2 to 10 μm, and the thickness of the PE layer is preferably in the range of 2 to 10 μm.

[0044] It is preferable to dispose a heat-resistant layer at least in one or more locations among the separator 40 (one or both sides), the positive electrode 20 (one or both sides), and the negative electrode 30 (one or both sides). The heat-resistant layer contains a filler and a binder. Examples of the filler include boehmite (alpha alumina), titania (rutile type or anatase type, in the case of anatase type, disposed so that the heat-resistant layer does not contact the negative electrode), zirconia, magnesia, aluminum hydroxide, magnesium hydroxide, zinc hydroxide, etc. Examples of the binder include acrylic resin, aramid, SBR, PTFE, etc. The content of the binder is preferably in the range of 2 to 30 mass % with respect to the total amount of the heat-resistant layer. The thickness of the heat-resistant layer is preferably in the range of, for example, 2 to 12 μm.

[0045] [Non-aqueous electrolyte] The non-aqueous electrolyte includes a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. The non-aqueous electrolyte is not limited to a liquid electrolyte (non-aqueous electrolyte solution), and may be a solid electrolyte using a gel-like polymer or the like. The non-aqueous solvent may be, for example, esters, ethers, nitriles such as acetonitrile, amides such as dimethylformamide, or a mixed solvent of two or more of these. The non-aqueous solvent may contain a halogen-substituted product in which at least a part of the hydrogen of these solvents is substituted with a halogen atom such as fluorine.

[0046] Examples of the esters include cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate; chain carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), methyl propyl carbonate, ethyl propyl carbonate, and methyl isopropyl carbonate; cyclic carboxylates such as γ-butyrolactone (GBL) and γ-valerolactone (GVL); and chain carboxylates such as methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), ethyl propionate, and γ-butyrolactone.

[0047] Examples of the ethers include 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, propylene oxide, 1,2-butylene oxide, 1,3-dioxane, 1,4-dioxane, 1,3,5-trioxane, furan, 2-methylfuran, 1,8-cineole, cyclic ethers such as crown ethers, 1,2-dimethoxyethane, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, dihexyl ether, ethyl vinyl ether, butyl vinyl ether, methyl phenyl ether, and the like. Examples of the halogen-substituted compounds include fluorinated cyclic carbonates such as fluoroethylene carbonate (FEC), fluorinated chain carbonates, and fluorinated chain carboxylates such as methyl fluoropropionate (FMP).

[0048] The electrolyte salt is preferably a lithium salt. Examples of lithium salts include LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiAlCl4, LiSCN, LiCF3SO3, LiCF3CO2, Li(P(C2O4)F4), LiPF 6-x (C n F 2n+1 )x(1 < x < 6, n is 1 or 2), LiB 10 Cl 10 、LiCl, LiBr, LiI, lithium chloroborane, lithium lower aliphatic carboxylate, borate salts such as Li2B4O7, Li(B(C2O4)F2), imide salts such as LiN(SO2CF3)2, LiN(C1F 2l+1 SO2)(C m F 2m+1 SO2){l, m are integers of 0 or more}, etc. Among these, from the viewpoints of ionic conductivity, electrochemical stability, etc., it is preferable to use LiPF6. The concentration of the lithium salt is preferably 0.8 to 1.8 mol per 1 L of the non-aqueous solvent.

[0049] <Examples> Hereinafter, the present disclosure will be further described by way of examples, but the present disclosure is not limited to these examples.

[0050] <Example 1> [Fabrication of the positive electrode] As the positive electrode active material, the general formula LiNi 0.70 Co 0.25 Al 0.05A lithium transition metal composite oxide represented by O2 was used. The positive electrode active material, acetylene black, and polyvinylidene fluoride were mixed in a solid content mass ratio of 98:1:1, and N-methyl-2-pyrrolidone (NMP) was used as a dispersion medium to prepare a positive electrode composite slurry. For the positive electrode core, a metal foil containing metal elements of Al: 93.4 mass%, Mn: 0.6 mass%, Cu: 4.5 mass%, and Mg: 1.5 mass%, with a thermal conductivity of 151 W / m·K and a thickness of 15 μm, was used. The positive electrode composite slurry was then applied to both sides of the positive electrode core, the coating was dried and compressed, and then cut to a specified electrode size to obtain a positive electrode with a positive electrode composite layer formed on both sides of the positive electrode core.

[0051] [Preparation of negative electrode] Graphite was used as the negative electrode active material. The negative electrode active material, sodium carboxymethylcellulose (CMC-Na), and styrene butadiene rubber (SBR) were mixed in a predetermined solid content mass ratio, and a negative electrode composite slurry was prepared using water as a dispersion medium. Next, the negative electrode composite slurry was applied to both sides of a negative electrode core made of copper foil, the coating was dried, compressed with a predetermined force, and then cut into a predetermined electrode size to obtain a negative electrode in which a negative electrode composite layer was formed on both sides of the negative electrode core.

[0052] [Preparation of non-aqueous electrolyte] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) were mixed in a volume ratio of 3:3:4 (25°C, 1 atm). LiPF6 was added to the mixed solvent to a concentration of 1.15M to obtain a non-aqueous electrolyte.

[0053] [Preparation of test cell] An aluminum lead was attached to the exposed core of the positive electrode, and a nickel lead was attached to the exposed core of the negative electrode, and the positive and negative electrodes were spirally wound with a separator interposed therebetween, and then pressed in the radial direction to produce a flat wound electrode body. This electrode body was housed in an exterior body made of an aluminum laminate sheet, and the nonaqueous electrolyte was injected, and the opening of the exterior body was sealed to obtain a test cell (nonaqueous electrolyte secondary battery).

[0054] The test cells thus obtained were subjected to performance evaluation (resistance increase rate in a high-load charge / discharge test, maximum temperature reached in a nail penetration test) by the following methods, and the evaluation results are shown in the table.

[0055] [High-load charge / discharge test (evaluation of resistance increase rate)] The test cell was charged to 4.2V at 0.1It in a 25°C environment, then discharged to 2.5V at 0.1It, and then charged to 3.7V. At that voltage, charging was performed at 2.5It for 240 seconds, and then discharging was performed at 30It for 20 seconds. The rest time between charging and discharging was 120 seconds. This charge / discharge cycle was performed 1000 times. The battery resistance after 1 cycle and the battery resistance after 1000 cycles were calculated as a relative value, and this was taken as the resistance increase rate in the charge / discharge cycle.

[0056] [Nail penetration test (evaluation of maximum temperature)] (1) The test cell was charged at a constant current of 0.1 It in an environment of 25° C. until the battery voltage reached 4.2 V, and then charging was continued at a constant voltage until the current value reached 0.05 It. (2) In an environment of 60°C, the tip of a round nail with a diameter of 3 mm was brought into contact with the center of the side of the cell charged in (1) and the nail was thrust into the battery in the thickness direction at a speed of 10 mm / sec. The thrust of the nail was stopped when the nail had completely penetrated the battery. (3) The cell temperature was measured at a position 10 mm away from the center of the side of the cell into which the round nail was pierced, and the maximum temperature reached was calculated.

[0057] <Examples 2 to 44 and Comparative Examples 1 and 2> The composition (thermal conductivity) of the positive electrode core, the composition of the positive electrode active material, or the circularity of the positive electrode active material were changed to those shown in Tables 1 to 4, and positive electrodes and test cells were prepared in the same manner as in Example 1, and the performance of the test cells was evaluated.

[0058] [Table 1]

[0059] [Table 2]

[0060] [Table 3]

[0061] [Table 4]

[0062] As shown in Tables 1 to 4, the test cells of the Examples all had a lower maximum temperature in the nail penetration test, indicating that heat generation was suppressed, compared to the test cell of Comparative Example 1. In addition, the test cells of the Examples all had a lower resistance increase rate compared to the test cell of Comparative Example 2. In other words, the test cells of the Examples can suppress heat generation in the battery when an internal short circuit occurs while keeping the battery resistance low, and can achieve both characteristics. [Explanation of symbols]

[0063] 10 Nonaqueous electrolyte secondary battery 11 Electrode body 12 Positive terminal 13 Negative terminal 14 Outer can 15 Sealing plate 16 Injection section 17 Gas exhaust valve 20 positive electrode 21 Positive electrode core 22 Positive electrode mixture layer 23,33 Exposed core part 24 Cathode active material 25 Positive electrode current collector 30 negative electrode 31 Negative electrode core 35 Negative electrode current collector 40 Separator 100 nails

Claims

1. A positive electrode comprising a core body and a composite layer formed on a surface of the core body, the mixture layer includes a positive electrode active material mainly composed of a lithium transition metal composite oxide in which a ratio of Ni to the total number of moles of metal elements excluding Li is 70 mol % or more, The core has a thermal conductivity X of 50 to 155 W / m K (25° C.), a thermal conductivity X of the core body, and a median value Y in a circularity distribution of the lithium transition metal composite oxide, the median value Y1 and the median value Y2 of the circularity distribution of the lithium transition metal composite oxide, the median value Y1 and the median value Y2 of the thermal conductivity X of the core body, respectively satisfying the conditions of the following (Formula 1) and (Formula 2), respectively. (Formula 1) Y1=0.9322 (X -0.987) (Formula 2) Y2=0.1613(X -0.746)-0.0005

2. 2. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein the core contains Mg, and the Mg content is 1.5 to 90 mass %.

3. 3. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein the lithium transition metal composite oxide includes a single particle constituted by one primary particle or constituted by an aggregation of five or less primary particles.

4. The lithium transition metal composite oxide further includes secondary particles formed by agglomeration of primary particles having a particle size smaller than that of the single-particle primary particles, 4. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 3, wherein a mass ratio of the single particles to the secondary particles is from 2:8 to 6:

4.

5. The lithium transition metal composite oxide is a single particle composed of one primary particle or composed of an aggregate of 5 or less primary particles, The single particles include a first single particle having a circularity of 0.9 or more and a second single particle having a circularity of less than 0.9, 3. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein a mass ratio of the first single particles to the second single particles is from 2:8 to 6:

4.

6. 6. A non-aqueous electrolyte secondary battery comprising: the positive electrode according to claim 1; a negative electrode; a separator interposed between the positive electrode and the negative electrode; and a non-aqueous electrolyte.

Citation Information

Patent Citations

  • JP1974053631A

  • Electrode structure for laminated secondary battery

    JP2000277087A

  • Non-aqueous electrolyte secondary battery

    JP2019083138A

  • JPP6600734B